Assessing Form Four Students' Attitude Towards Science In North East District Of Penang - Chin, Sook Fui (2012)
This study aimed to adapt and validate an ATS measure, assess students’ ATS, and investigate the effect of track position on students’ ATS. A total of 749 Form Four students from eight secondary schools in the state of Penang, Malaysia were involved in this study. An ATS measure, namely Attitude towards Science Scale (ATSS) was adapted from Test of Science-Related Attitude, TOSRA (Fraser, 1981) and Attitude towards Science Measure, ATSM (Kind, Jones, & Barmby, 2007) upon considerations of appropriateness, theoretical framework, and psychometric properties.